Role of Central Nervous System Prophylaxis in Primary Testicular Diffuse Large B-cell Lymphoma in Reducing Risk of Central Nervous System Relapse: A Systematic Review and Meta-analysis - Salem Bahashwan (Journal of Applied Hematology)
BACKGROUND: Primary testicular diffuse large B-cell lymphoma (PT-DLBCL) is associated with a significant risk of central nervous system (CNS) relapse. CNS prophylaxis strategies, such as high-dose methotrexate (HD-MTX) and intrathecal (IT) chemotherapy, are commonly implemented, though their effectiveness remains uncertain. AIM: This meta-analysis evaluates the efficacy of CNS prophylaxis strategies– HD-MTX, IT chemotherapy, and no prophylaxis – in reducing risk of CNS relapse in primary testicular DLBCL patients treated with rituximab and chemotherapy. MATERIALS AND METHODS: A systematic search was conducted in major medical databases to identify studies reporting CNS relapse rates in patients with primary testicular DLBCL undergoing CNS prophylaxis. Inclusion criteria specified studies of adult patients without initial CNS involvement, treated with rituximab and chemotherapy. A random-effects model was used to calculate pooled CNS relapse rates, and sensitivity analyses were performed to assess the robustness of findings. RESULTS: Eleven studies involving 245 patients were included. The pooled analysis showed a CNS relapse risk ratio (RR) of 0.36 (95% confidence interval [CI]: −0.62–1.33) for the HD-MTX group, suggesting a potential reduction in relapse risk. The IT chemotherapy group had a RR of 0.59 (95% CI: −0.21–1.39), with moderate heterogeneity. CONCLUSION: HD-MTX and IT chemotherapy show trends toward reduced CNS relapse risk in primary testicular DLBCL, although evidence remains inconclusive due to heterogeneity and study design limitations. This analysis highlights the need for large, prospective trials to confirm the optimal CNS prophylaxis strategy in this high-risk population.